Arbuscular mycorrhizal fungi combined with exogenous calcium improves the growth of peanut (Arachis hypogaea L.) seedlings under continuous cropping - Li CUI; Feng GUO; Jia-lei ZHANG; Sha YANG; Jing-jing MENG; Yun GENG; Quan WANG; Xin-guo LI; Shu-bo WAN (Journal of Integrative Agriculture, 2019)
The growth and yield of peanut are negatively affected by continuous cropping. Arbuscular mycorrhizal fungi (AMF) and calcium ions (Ca2+) have been used to improve stress resistance in other plants, but little is known about their roles in peanut seedling growth under continuous cropping. This study investigated the possible roles of the AMF Glomus mosseae combined with exogenous Ca2+ in improving the physiological responses of peanut seedlings under continuous cropping. G. mosseae combined with exogenous Ca2+ can enhance plant biomass, Ca2+ level, and total chlorophyll content. Under exogenous Ca2+ application, the Fv/Fm in arbuscular mycorrhizal (AM) plant leaves was higher than that in the control plants when they were exposed to high irradiance levels. The peroxidase, superoxide dismutase, and catalase activities in AM plant leaves also reached their maximums, and accordingly, the malondialdehyde content was the lowest compared to other treatments. Additionally, root activity, and content of total phenolics and flavonoids were significantly increased in AM plant roots treated by Ca2+ compared to either G. mosseae inoculation or Ca2+ treatment alone. Transcription levels of AhCaM, AhCDPK, AhRAM1, and AhRAM2 were significantly improved in AM plant roots under exogenous Ca2+ treatment. This implied that exogenous Ca2+ might be involved in the regulation of G. mosseae colonization of peanut plants, and in turn, AM symbiosis might activate the Ca2+ signal transduction pathway. The combination of AMF and Ca2+ benefitted plant growth and development under continuous cropping, suggesting that it is a promising method to cope with the stress caused by continuous cropping.